Current and future impact of COVID-19 pandemic lockdowns on the confidence level of clinical practice among female dental students in Namakkal district - A cross-sectional study - Shanmathi Sundararajan; Girish R Shavi; Shankar Shanmugam; Lalithambigai Gunasekaran; SenthilKumar Sennan (Wolters Kluwer Medknow Publications, 2023)
Introduction: Coronavirus has influenced the health-care system and human life in several aspects. Education being an important factor has decreased the level of interest and confidence among the students. Objective: The objective of this study was to assess the impact of the COVID pandemic on the self-confidence level of clinical practice. Materials and Methods: A cross-sectional study was conducted among 120 female dental students in the Namakkal district. Students were selected using a simple random sampling lottery method. Their level of self-confidence was assessed using a pretested questionnaire framed in all specialties regarding clinical work. The questionnaire was distributed via Google Forms and evaluated using a five-point Likert scale. Results: Among 120 students, a higher level of confidence was seen in endodontic procedures followed by periodontics. A lower level of confidence was seen in managing dental emergencies and procedures such as pulpotomy/pulpectomy and extractions. Only 24% were confident in class I cavity preparation, 30% in instructing patients about oral hygiene, 13% in recording case history, and 6.7% in fluoride application. Most of the students wish to improve their level of confidence through extra training because only 20% were satisfied with their self-confidence. Conclusion: In the field of dentistry, contact with clinical practice has been severely affected, and it is understood that online educational platforms can only improve the theoretical part and have lower performance in clinical education.